The Dynamics of Job Crafting, Meaningful Work, and Work Engagement in Predicting Turnover Intention: Evidence from the Digital Creative Industry - Meyreza Dwi Savitri; Widya Parimita; Rd. Tuty Sariwulan (Journal of Strategic Innovation in Economics and Business, 2026)
The digital creative industry landscape in Indonesia currently faces significant talent retention challenges, especially among Generation Z workers who have different psychological expectations. This study aims to critically analyze the influence of Job Crafting and Meaningful Work on Turnover Intention, with Work Engagement as a crucial mediating variable. Using a quantitative approach with the Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) method, this study takes the microcosm at FEB Digital Agency as its object of study. The results of the analysis show that all of the proposed hypotheses are accepted: Job Crafting and Meaningful Work are proven to have a negative and significant effect on Turnover Intention, both directly and indirectly through Work Engagement. An interesting finding reveals that Job Crafting is the strongest single predictor of Work Engagement (t = 6.429), while Work Engagement is the most dominant barrier to attrition in this model (β = -0.456). This indicates that employee engagement is not merely an operational phenomenon, but rather the result of job personalization and the perception of existential value. This study concludes that effective retention strategies must focus on the transition from control-based management to empowerment-based management that supports work autonomy and the articulation of real work meaning.